2000
DOI: 10.2307/1543187
|View full text |Cite
|
Sign up to set email alerts
|

Development of embryonic cells containing serotonin, catecholamines, and FMRFamide-related peptides in Aplysia californica

Abstract: This study demonstrates the presence of a relatively extensive but previously unrecognized nervous system in embryonic stages of the opisthobranch mollusc Aplysia californica. During the trochophore stage, two pairs of cells were observed to be reactive to antibodies raised against the neuropeptides FMRFamide and EFLRIamide. These cells were located in the posterior region of the embryo, and their anterior projections terminated under the apical tuft. As the embryos developed into veliger stages, serotonin-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
90
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 63 publications
9
90
0
1
Order By: Relevance
“…More recently, Braubach et al [2006] showed that serotonergic input enhances ciliary beating and thus increases both locomotion and feeding of gastropod larvae, consistent with earlier studies showing that serotonin enhances swimming in bivalve larvae [Beiras and Widdows, 1995a]. These results are also consistent with previous studies of serotonergic projections to the foot of larval gastropods [Goldberg and Kater, 1989;Voronezhskaya and Elekes, 1993;Kempf et al, 1997;Marois and Carew, 1997c;Dickinson et al, 1999Dickinson et al, , 2000 and bivalves [Croll et al, 1997;Plummer, 2002;Voronezhskaya et al, 2008] where similar excitatory effects on cilia have been noted [Diefenbach et al, 1991;Kuang and Goldberg, 2001].…”
Section: Neurons First Appear Early In Larval Developmentsupporting
confidence: 86%
See 1 more Smart Citation
“…More recently, Braubach et al [2006] showed that serotonergic input enhances ciliary beating and thus increases both locomotion and feeding of gastropod larvae, consistent with earlier studies showing that serotonin enhances swimming in bivalve larvae [Beiras and Widdows, 1995a]. These results are also consistent with previous studies of serotonergic projections to the foot of larval gastropods [Goldberg and Kater, 1989;Voronezhskaya and Elekes, 1993;Kempf et al, 1997;Marois and Carew, 1997c;Dickinson et al, 1999Dickinson et al, , 2000 and bivalves [Croll et al, 1997;Plummer, 2002;Voronezhskaya et al, 2008] where similar excitatory effects on cilia have been noted [Diefenbach et al, 1991;Kuang and Goldberg, 2001].…”
Section: Neurons First Appear Early In Larval Developmentsupporting
confidence: 86%
“…In all cases, these cells appear to contain FMRFamide-related peptides and have axons that project anteriorly along each side of the body wall to meet near the ASO and the later developing cerebral and pedal ganglia Voronezhskaya, 1995, 1996a, b;Dickinson et al, 1999Dickinson et al, , 2000Dickinson and Croll, 2003]. Although such posterior, peptidergic cells appear to be a general feature of gastropod larvae, their presence in other molluscs is less consistent.…”
Section: Neurons First Appear Early In Larval Developmentmentioning
confidence: 98%
“…More recently, Mackie et al (Mackie et al, 1976) and Marois and Carew (Marois and Carew, 1997b) used electron microscopy to confirm innervation of pre-oral cells in Mangelia nebula and Aplysia californica, and in the latter species, demonstrated that serotonergic fibres contributed to such innervation. In fact, immunocytochemical studies have now demonstrated serotonergic innervation of the vela of various gastropods (Dickinson et al, 2000; Larval molluscs commonly use ciliated vela to swim and feed. In this study we used immunohistochemistry to demonstrate innervation of velar cilia and muscles by monoaminergic and peptidergic fibres in the caenogastropod, Ilyanassa obsoleta.…”
Section: Introductionmentioning
confidence: 99%
“…Although these findings may be generally applicable to closely related species (Uhler et al, 2000), questions arise about whether direct-developing pulmonate gastropods are representative models for understanding the control of ciliary activity on vela of freeliving molluscan larvae. In particular, ciliated cells on the foot of H. trivolvis are only known to possess serotonergic innervation whereas serotonergic, catecholaminergic and peptidergic axons extend into the vela of larval caenogastropods (Dickinson and Croll, 2003;Dickinson et al, 1999;Page and Parries, 2000), heterobranch gastropods (Dickinson et al, 2000;Kempf et al, 1997) and bivalves (Croll et al, 1997;Plummer, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their microscopic size and relatively simple structure, trochophores display a considerable repertoire of complex behavioural action patterns that are mediated by a centralized nervous system and peripheral sensory receptors (Kempf et al 1997). Studies on neuronal development in larval Trochozoa have shown that they possess a well-developed nervous system, which generally includes several centres: cerebral ganglia, ventral cords and prototroch nerve (Å kesson 1967;Lacalli 1981Lacalli , 1984Lacalli , 1986Barlow & Truman 1992;Kempf et al 1992;Hay-Schmidt 1995;Dickinson et al 2000;Voronezhskaya et al 2002Voronezhskaya et al , 2003. This system obviously has to detect and process incoming environmental stimuli.…”
Section: Introductionmentioning
confidence: 99%